Makassar Police Satreskrim Efforts Against Health Protocols in Criminal Investigations to Reduce Covid-19 Transmission - Muh. Ammar Riswandha Prajamanggala (Indonesian Journal of Police Studies, 2021)
The research focus of this thesis is motivated by the phenomenon of the Covid-19 Pandemic which has become a disease with rapid transmission that can cause death. In addition, the process of investigating criminal acts must continue in accordance with the Main Duties of the Police. According to Article 13 of Law no. 2 of 2002, namely law enforcement. Therefore, a study was conducted that aims to describe the process of investigating criminal acts, applying health protocols in investigations and identifying factors that hinder the application of health protocols in investigations. The theories and concepts used by the author in answering the problems are the theory of law enforcement, the theory of investigation, the theory of legal effectiveness and the concept of health protocols. This research was conducted with a qualitative approach and used a descriptive analysis type of research. The findings of this study are that the investigation is still carried out according to Perkap 6 of 2019 which is analyzed according to the optimal investigation theory. The application of health protocols in the investigation was analyzed according to law enforcement theory and the effectiveness of the law was not optimal. The inhibiting factors are the absence of investigation SOPs, human resources, budget, culture / habits of officers. Based on the results of the study, the authors suggest making SOPs for Investigations, tracing suspects after being outside the Polrestabes environment, routine swabs of Opsnal members and making new formulations related to the implementation of virtual examinations.